2003
DOI: 10.1523/jneurosci.23-14-06063.2003
|View full text |Cite
|
Sign up to set email alerts
|

Light-Evoked Excitatory and Inhibitory Synaptic Inputs to ON and OFF α Ganglion Cells in the Mouse Retina

Abstract: Bipolar cell and amacrine cell synaptic inputs to alpha ganglion cells (alphaGCs) in dark-adapted mouse retinas were studied by recording the light-evoked excitatory cation current (DeltaIC) and inhibitory chloride current (DeltaICl) under voltage-clamp conditions, and the cell morphology was revealed by Lucifer yellow fluorescence with a confocal microscope. Three types of alphaGCs were identified. (1) ONalphaGCs exhibits no spike activity in darkness, increased spikes in light, sustained inward DeltaIC, sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

39
267
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(307 citation statements)
references
References 50 publications
39
267
1
Order By: Relevance
“…We tested these predictions by simultaneously measuring synaptic input to an AII amacrine cell (held at the reversal potential for inhibitory synaptic input) and an Off RGC (held at the reversal potential for excitatory synaptic input) evoked by steps in light intensity from darkness; we focused on Off transient RGCs, a class of RGC distinguished by its large soma and transient bursts of action potentials at light offset 8,16,24 . The amplitude of excitatory synaptic input to AII amacrine cells and the IPSC in Off transient RGCs differed by more than an order of magnitude (Fig.…”
Section: Circuitry Governing Synaptic Input To On and Off Rgcsmentioning
confidence: 99%
“…We tested these predictions by simultaneously measuring synaptic input to an AII amacrine cell (held at the reversal potential for inhibitory synaptic input) and an Off RGC (held at the reversal potential for excitatory synaptic input) evoked by steps in light intensity from darkness; we focused on Off transient RGCs, a class of RGC distinguished by its large soma and transient bursts of action potentials at light offset 8,16,24 . The amplitude of excitatory synaptic input to AII amacrine cells and the IPSC in Off transient RGCs differed by more than an order of magnitude (Fig.…”
Section: Circuitry Governing Synaptic Input To On and Off Rgcsmentioning
confidence: 99%
“…Inhibitory transmission to ganglion cells is known to have different effects, including reducing activity (6, 10), or increasing activity through disinhibition (11)(12)(13)(14). Thus, to understand how a particular amacrine cell changes the ganglion cell response, measurements of both the response and transmission of the interneuron must be temporally precise.A common approach to understand how interneurons influence a neural circuit is to study their combined inputs by voltage clamping the postsynaptic cell (6,8,13). In this regard, recordings from retinal ganglion cells have revealed that inhibitory neurotransmission can suppress activity and that relief from inhibition can generate activity (12)(13)(14).…”
mentioning
confidence: 99%
“…Inhibitory transmission to ganglion cells is known to have different effects, including reducing activity (6, 10), or increasing activity through disinhibition (11)(12)(13)(14). Thus, to understand how a particular amacrine cell changes the ganglion cell response, measurements of both the response and transmission of the interneuron must be temporally precise.…”
mentioning
confidence: 99%
See 2 more Smart Citations